2017
DOI: 10.1136/injuryprev-2016-042272
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the resistance to creating safer ice hockey: essential points for injury prevention

Abstract: Using structural functionalist theory, we propose an argument that the unfortunate perpetuation of violence and body checking in youth ice hockey serves to maintain the social order of the game and its culture. Any strategies aimed at modifying and promoting healthy behaviour in the game should take these concepts into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In response, Carless and Douglas have suggested that team managers, coaches, league governing bodies, other athletes and researchers need to support alternative narratives that support athletes' long-term development and well being, even once their athletic career ends [31,32]. According to Todd et al, the majority of concussions in hockey are caused by body checking [47]. Despite the known negative outcome, there is a resistance to removing body checking from hockey.…”
Section: Discussionmentioning
confidence: 99%
“…In response, Carless and Douglas have suggested that team managers, coaches, league governing bodies, other athletes and researchers need to support alternative narratives that support athletes' long-term development and well being, even once their athletic career ends [31,32]. According to Todd et al, the majority of concussions in hockey are caused by body checking [47]. Despite the known negative outcome, there is a resistance to removing body checking from hockey.…”
Section: Discussionmentioning
confidence: 99%
“…48 Moreover, to our knowledge, only 1 study has assessed differences in head impact exposures during games and practices among youth flag football athletes. 29 As there are observed differences between practice and games in athlete and coach behavior, such as reduced concussion reporting by athletes and greater use of aggressive actions during games, 11,12,45 further investigation is warranted. 22 The goal of this study was to expand upon what is currently known about head impact exposure among youth tackle and flag football athletes during both practices and games.…”
mentioning
confidence: 99%